2017
DOI: 10.1002/2016jc012177
|View full text |Cite
|
Sign up to set email alerts
|

Tsunamis generated by long and thin granular landslides in a large flume

Abstract: In this experimental study, granular material is released down slope to investigate landslide‐generated waves. Starting with a known volume and initial position of the landslide source, detailed data are obtained on the velocity and thickness of the granular flow, the shape and location of the submarine landslide deposit, the amplitude and shape of the near‐field wave, the far‐field wave evolution, and the wave runup elevation on a smooth impermeable slope. The experiments are performed on a 6.7 m long 30° slo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
77
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(93 citation statements)
references
References 41 publications
13
77
0
1
Order By: Relevance
“…The wave characteristics are dependent on the landslide impact parameters [Fritz et al, 2003a[Fritz et al, , 2003b[Fritz et al, , 2004Zweifel et al, 2006;Heller and Hager, 2010;Mohammed and Fritz, 2012;McFall and Fritz, 2016;Bregoli et al, 2017;Miller et al, 2017]. The governing tsunami generation parameters investigated in this study are the water depth h, slide impact velocity v s , slide thickness s, slide width b, slide volume V s , slide length scale L s 5 V s /(sb), and shoreline radius r c .…”
Section: Physical Modelmentioning
confidence: 99%
“…The wave characteristics are dependent on the landslide impact parameters [Fritz et al, 2003a[Fritz et al, , 2003b[Fritz et al, , 2004Zweifel et al, 2006;Heller and Hager, 2010;Mohammed and Fritz, 2012;McFall and Fritz, 2016;Bregoli et al, 2017;Miller et al, 2017]. The governing tsunami generation parameters investigated in this study are the water depth h, slide impact velocity v s , slide thickness s, slide width b, slide volume V s , slide length scale L s 5 V s /(sb), and shoreline radius r c .…”
Section: Physical Modelmentioning
confidence: 99%
“…Moreover, large and fast landslides often generate greater wave amplitudes, as indicated by laboratory experiments (e.g., Fritz et al, 2003aFritz et al, , 2003b and the numerical results in section 3.3. Notably, Miller et al (2017) and Meng (2018) suggested that the wave amplitudes of long and thin granular landslides are mainly affected by the effective mass, which is defined as the landslide mass entering the water body at the moment that the leading wave reaches its maximum wave height. Figures S21 and S22 show the dependence of e on the initial landslide volume and velocity, respectively, which are normalized by bh 2 w0 and ffiffiffiffiffiffiffiffiffi gh w0 p , respectively.…”
Section: Water Resources Researchmentioning
confidence: 99%
“…Experiments were performed in a landslide flume consisting of an 8.23 m long slope inclined at 30 • to the horizontal to gravitationally accelerate landslides into a 33.0 m long and 2.1 m wide horizontal wave flume described in detail by [12], shown in Figure 1. Tests with different mobility were selected as end-member examples in the present study.…”
Section: Laboratory Experimentsmentioning
confidence: 99%
“…where the sliding mass with bulk density ρ s impacts the water on slope α at velocity v s parallel to the slope. It has thickness s on impact with the water, and the resulting wave is generated over the effective time ∆t e that momentum is imparted from the slide to the water [12]. The fluid momentum flux (M f ) is given by:…”
Section: Theoretical Momentum Balancementioning
confidence: 99%